Phylogenetic analysis and expression patterns of Pax genes in the onychophoran Euperipatoides rowelli reveal a novel bilaterian Pax subfamily. Issue 1 (January 2015) - Franke, Franziska Anni; Schumann, Isabell; Hering, Lars; Mayer, Georg
SUMMARY Pax family genes encode a class of transcription factors that regulate various developmental processes. To shed light on the evolutionary history of these genes in Panarthropoda (Onychophora + Tardigrada + Arthropoda), we analyzed the Pax repertoire in the embryonic and adult transcriptomes of the onychophoran Euperipatoides rowelli. Our data revealed homologs of all five major bilaterian Pax subfamilies in this species, including Pax2/5/8, Pax4/6, Pox‐neuro, Pax1/9/Pox‐meso, and Pax3/7. In addition, we identified a new Pax member, pax‐α, which does not fall into any other known Pax subfamily but instead clusters in the heterogenic Pax‐α/β clade containing deuterostome, ecdysozoan, and lophotrochozoan gene sequences. These findings suggest that the last common bilaterian ancestor possessed six rather than five Pax genes, which have been retained in the panarthropod lineage. The expression data of Pax orthologs in the onychophoran embryo revealed distinctive patterns, some of which might be related to their ancestral roles in the last common panarthropod ancestor, whereas others might be specific to the onychophoran lineage. The derived roles include, for example, an involvement of pax2/5/8, pox‐neuro, and pax3/7 in onychophoran nephridiogenesis, and an additional function of pax2/5/8 in the formation of the ventral and preventral organs. Furthermore, our transcriptomic analyses suggest that at least some Pax genes, including pax6 and pax‐α, are expressed in the adult onychophoran head, although the corresponding functions remain to be clarified. The remarkable diversity of the Pax expression patterns highlights the functional and evolutionary plasticity of these genes in panarthropods.